Analytical modeling for offshore composite rubber hose with spiral stiffeners under internal pressure. (May 2021) - Gao, Pan; Gao, Qiang; An, Chen; Zeng, Ji
Internal pressure is the most important functional load for the offshore composite rubber hose. In this paper, the stress and radial displacement of the hose under internal pressure are investigated. The hose dimensions are length of 10.7 m and nominal bore diameter of 500 mm. The composite structure is mainly composed of cord-rubber reinforcement layers and a spiral steel stiffener. To calculate the stress and deformation of the hose, the stiffener and composite cord-rubber layers are theoretically analyzed based on the Euler–Bernoulli beam theory and the Donnell shell theory, respectively. The stiffener distinguishes the hose from common filament wound un-stiffened composite pipes in regard to the stress distribution and radial deformation. It is found that the stiffener plays an important role in affecting the mechanical behavior of composite reinforcement. Influences of the cord-winding angle, the stiffener spacing, and the stiffener's tensile stiffness on the axial, hoop and shear stresses, and the radial displacement are investigated. The analytical model shows a good agreement with the finite element model. It is supposed to be of significant reference for practical engineering.